Protection of Consumer Rights in Tourist Bus Accident Cases Through the Restorative Justice Approach - Febriani, Risma Dwi; Hutabarat, Sylvana Murni Deborah (Journal of Law, Politic and Humanities, 2025)
The Trans Putera Fajar tourist bus accident in Subang resulted in losses with fatalities, serious injuries, minor injuries, and damage to the vehicle. The study aims to learn about the protection of consumer rights applied in tourist bus accident cases based on the principle of the restorative justice approach. The case study used normative legal research methods and approaches, namely legal analysis. The results of the study provide an explanation regarding consumer protection in tourist bus accident cases that can be applied through a restorative justice approach agreed upon by all victims by providing compensation as a form of the perpetrator's responsibility to restore the situation and supported by the decision of the Subang District Court which still provides sanctions for the perpetrators by applicable regulations. The conclusion is that the suitability between the principle of restorative justice and consumer protection can be applied peacefully between the parties without eliminating the demands for punishment for the perpetrators